The Effects Of Self Esteem, Social Support, And Religious Orientation Toward Cyberbullying Intention On Adolescents At Senior High School - Kinanti, Diah Roro; Hartati, Netty (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2017)
Cyberbullying intention has penetrated into adolescence and even in the school environment. Moreover, coupled with the widespread use of smartphones among adolescents. Number of Internet users in 2014 in Banten province and 3.3 million users in the age of 10-24 years of as much as 75.5%. Subjects of this study are 210 high school students in the area of Triguna Utama School. This study showed various results of cyberbullying intention variance proportion that affected by self-esteem, emotional support, instrumental support, informational support, companionship support, intrinsic orientation and ekstrinsic orientation which is 17,9% with the significant contribution variable as follows: companionship support, intrinsic orientation, and ekstrinsic orientation.Â DOI: 10.15408/tazkiya.v22i2.8400